Insulated, impact-resistant medium voltage power cable and method for producing the same

CN122907418APending Publication Date: 2026-10-13NANCHANG CABLE(NANNING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611199840.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种绝缘耐冲击的中压电力电缆及其制备方法,用于解决在现有技术中的电力电缆的耐冲击强度、电气强度及低温韧性有待进一步提高的技术问题

Benefits of technology

1、本发明中,烯烃修饰杂化硅氧烷中的咔唑基团借助共轭杂环构筑深能级电荷陷阱,三氟丙基与苯基共缩聚形成氟硅芳杂化聚硅氧烷网络,二者协同抑制空间电荷积聚并增强链段刚性,甲基丙烯酰氧基在过氧化物引发下与聚乙烯原位接枝交联,于基体中构建有机-无机互穿网络,电荷陷阱、刚性网络与互穿网络三者耦合,在强电场下有效分散电树枝通道并阻滞裂纹扩展,显著提高了绝缘层单位厚度冲击击穿电压与工频电气强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses an insulating and impact-resistant medium-voltage power cable and a preparation method thereof, and belongs to the technical field of power cable processing, and is used for solving the technical problem that the impact strength, electrical strength and low-temperature toughness of the power cable in the prior art need to be further improved, and specifically comprises a plurality of groups of insulating wire cores, the insulating wire core is obtained by adopting three-layer co-extrusion coating of semi-conductive shielding material, insulating material and outer semi-conductive shielding material on the outer side of a cable core conductor. In the application, first, an olefin modified hybrid siloxane containing a carbazole group, a trifluoropropyl group and a phenyl group is prepared, then the modified polyethylene particles are obtained by melt grafting of the low-density polyethylene, then the insulating material is prepared by absorption of a crosslinking agent, then the cable core is coated by three-layer co-extrusion, then the steam crosslinking, armoring and sheath forming are performed, and finally, the insulating and impact-resistant medium-voltage power cable is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power cable processing technology, specifically to an insulated and impact-resistant medium-voltage power cable and its preparation method. Background Technology

[0002] As a key transmission carrier for urban power grids and industrial power distribution systems, the reliability of the insulation system of medium-voltage power cables directly determines the safety of power grid operation. With the upgrading of distribution network voltage levels and the large-scale integration of new energy sources, medium-voltage cables not only need to meet the conventional power frequency withstand voltage requirements, but also need to maintain insulation integrity under complex working conditions such as lightning strikes, mechanical collisions, and low-temperature laying. The development has now shifted from simply pursuing electrical strength to the synergistic improvement of multiple performance aspects such as electrical, mechanical, and environmental properties, which places higher demands on the impact resistance, space charge suppression capability, and low-temperature toughness of insulation materials.

[0003] Currently, medium-voltage cable insulation layers are mostly based on cross-linked polyethylene. To improve their resistance to electrical treeing and impact, the industry often uses inorganic nanofillers for physical blending, adds small molecule voltage stabilizers, or uses processes such as radiation cross-linking and silane cross-linking for modification. However, nanofillers have poor interfacial compatibility with polyolefin matrices and are prone to agglomeration, forming interfacial defects. Furthermore, small molecule voltage stabilizers are prone to migration and precipitation under the influence of electric and thermal fields, resulting in insufficient long-term stability. At the same time, although radiation cross-linking can improve the degree of cross-linking, it is highly dependent on equipment and difficult to achieve deep and uniform cross-linking. The above methods are still difficult to achieve synergistic optimization in suppressing space charge accumulation, dispersing electrical treeing channels, and improving low-temperature toughness.

[0004] Meanwhile, under a strong electric field, cross-linked polyethylene is also prone to electric field distortion due to space charge injection and accumulation, which in turn induces the growth of electric trees and penetrates the insulation layer along weak paths. In addition, the organic and inorganic phase interfaces in traditional physical blending systems lack chemical bonding, and under low temperature or impact loads, stress concentration is easily caused by modulus mismatch and interface debonding, leading to embrittlement and cracking of the insulation layer. Furthermore, the interface electric field transition between the insulation layer and the semiconductive shielding layer in the insulated wire core is not smooth, and the local electric field enhancement is prone to causing partial discharge and accelerating insulation aging.

[0005] To address this technical deficiency, a solution is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide an insulated and impact-resistant medium-voltage power cable and its manufacturing method, which solves the technical problem that the impact resistance, electrical strength and low-temperature toughness of power cables in the prior art need to be further improved.

[0007] The objective of this invention can be achieved through the following technical solution: an insulated and impact-resistant medium-voltage power cable, comprising several sets of insulated cores, wherein the insulated cores are obtained by three-layer co-extrusion of a semi-conductive shielding material, an insulating material, and an outer semi-conductive shielding material onto the outside of the cable core conductor; The insulating material is prepared by the following steps: A1. Low-density polyethylene and olefin-modified hybrid siloxane are mixed evenly in a high-speed mixer, then transferred to a twin-screw extruder for melt blending, extrusion and granulation to obtain modified polyethylene granules; A2. The modified polyethylene particles and the initiator are placed in a reactor and mixed. The reactor is heated to 50-70℃ and the mixture is absorbed for 2-6 hours. The insulation material is then obtained through post-treatment.

[0008] Furthermore, the medium-voltage power cable also includes a metal shielding layer, an inner lining layer, a galvanized steel wire armor layer, and an outer sheath layer.

[0009] Furthermore, in step A1, the weight ratio of the low-density polyethylene to the olefin-modified hybrid siloxane is 80-100:8-15.

[0010] Further, in step A2, the weight ratio of the modified polyethylene particles to the initiator is 90-100:0.05-0.1, and the initiator is one or both of dicumyl peroxide and 2,5-dimethyl-2,5-di-tert-butylperoxide. The post-processing steps include: after mixing and absorption, the product is cooled, pelletized, vacuum dried at 40-50°C for 4-8 hours, and sealed for storage to obtain the insulating material.

[0011] Furthermore, the olefin-modified hybrid siloxane is prepared by the following steps: B1. Place 3-amino-9-ethylcarbazole and toluene in a reaction vessel under nitrogen atmosphere and stir. Add 3-[(2,3)-epoxypropoxy]propylmethyldimethoxysilane and salicylic acid. Heat the reaction vessel to 110-120℃ and keep it at the temperature for 16-20h. After post-treatment, carbazole siloxane intermediate is obtained. B2. Place the carbazole-based siloxane intermediate and toluene in a reaction vessel and stir. Add trifluoropropyltrimethoxysilane and methylphenyldimethoxysilane, stir at room temperature for 10-20 min, add ethanol and deionized water, stir at room temperature for 30-60 min, add dibutyltin dilaurate, heat the reaction vessel to 50-60℃, keep the reaction at this temperature for 1-2 h, then heat the reaction vessel to 75-85℃, keep the reaction at this temperature for 3-5 h, and then perform post-treatment to obtain carbazole-based hybrid polysiloxane. B3. Carbazole-modified polysiloxane and dichloromethane were placed in a nitrogen-protected reactor and stirred. Triethylamine, 4-dimethylaminopyridine and hydroquinone monomethyl ether were added. The reactor was kept in an ice bath at 0-5°C. Methacrylamide chloride was added. The reactor was allowed to return to room temperature and reacted in the dark for 6-12 hours. The olefin-modified hybrid siloxane was then obtained after post-treatment.

[0012] Further, in step B1, the ratio of 3-amino-9-ethylcarbazole, toluene, 3-[(2,3)-epoxypropoxy]propylmethyldimethoxysilane and salicylic acid is 8.5-9.5g:150-200mL:23-25g:0.2-0.5g. The post-processing step includes: after the reaction is completed, wait for the reaction solution to cool to 50-60℃, filter to remove insoluble matter, transfer the filtrate to a rotary evaporator at a temperature of 60-70℃, and evaporate under reduced pressure until no liquid is collected to obtain carbazole siloxane intermediate.

[0013] The reaction formula for the preparation of olefin-modified hybrid siloxanes is as follows: In the formula: Further, in step B2, the ratio of the carbazolylsiloxane intermediate, toluene, trifluoropropyltrimethoxysilane, methylphenyldimethoxysilane, ethanol, deionized water, and dibutyltin dilaurate is 20-22g:80-120mL:2-5g:3-7g:20-30mL:5-8mL:0.06-0.12g. The post-processing step includes: after the reaction is completed, the reaction system is cooled to room temperature and transferred to a rotary evaporator at a temperature of 50-60℃ to remove the solvent by rotary evaporation under reduced pressure to obtain carbazolyl hybrid polysiloxane.

[0014] Further, in step B3, the ratio of the carbazole-modified polysiloxane, dichloromethane, triethylamine, 4-dimethylaminopyridine, hydroquinone monomethyl ether, and methacryloyl chloride is 24-26g:150-250mL:4.5-6.5g:0.15-0.25g:0.015-0.030g:4-6g. The post-processing steps include: after the reaction is completed, the reaction system is cooled to 0-10℃, and saturated sodium bicarbonate aqueous solution is slowly added to neutralize it. The reaction solution is transferred to a separatory funnel, and the organic phase is washed 1-3 times with deionized water and saturated brine. After drying with anhydrous sodium sulfate and filtration, the phase is transferred to a rotary evaporator at a temperature of 35-45℃ and evaporated under reduced pressure in the dark until no liquid is collected, thus obtaining the olefin-modified hybrid siloxane.

[0015] This invention also proposes a method for preparing an insulated, impact-resistant medium-voltage power cable, comprising the following steps: S1. Multiple strands of annealed copper wire are tightly twisted into a circular shape to obtain the cable core conductor; S2. Semiconductor shielding material, insulating material and outer semiconductor shielding material are simultaneously extruded onto the outside of the cable core conductor using a three-layer co-extrusion device, and then transferred to a cross-linking tube for heating cross-linking and cooling shaping to obtain an insulated wire core; the insulating material includes low-density polyethylene, olefin-modified hybrid siloxane and initiator. S3. Wrap the semiconducting resistive water tape around the outside of several sets of insulated wire cores, and then cover it with a loosely woven copper mesh to obtain a metal shielding layer. S4. Extrude the inner lining material onto the outside of the metal shielding layer to form the inner lining layer, and then tightly wrap the galvanized steel wire around the outside of the inner lining layer to obtain the galvanized steel wire armor layer. S5. The outer sheath material is extruded onto the outside of the galvanized steel wire armor layer, and after being cooled and shaped in a water tank, an insulated and impact-resistant medium-voltage power cable is obtained.

[0016] Furthermore, in step S1, the diameter of the single wire of the multi-strand annealed copper wire is 0.5-2.5mm, and the number of strands is 19-61.

[0017] Furthermore, in step S2, the extrusion thickness of the insulating material is 2.5-5.0 mm, the extrusion thickness of the semiconductive shielding material is 0.5-1.0 mm, the extrusion thickness of the outer semiconductive shielding material is 0.5-1.0 mm, the extrusion temperature of the three-layer co-extrusion is 180-220℃, the heating crosslinking is steam crosslinking, and the crosslinking temperature is 300-400℃. Both the semiconductive shielding material and the outer semiconductive shielding material are crosslinked polyethylene-based semiconductive shielding materials.

[0018] Furthermore, in step S3, the semiconducting resistive water tape is wrapped in 1-2 layers.

[0019] Furthermore, in step S4, the inner lining material is low-density polyethylene, the diameter of the galvanized steel wire is 1.0-2.5mm, and the wrapping pitch is 10-20mm. The galvanized steel wire is obtained by pre-processing armor steel wire with continuous anti-corrosion treatment. The continuous anti-corrosion treatment includes: sequentially pickling, washing, anodic electrolytic activation, and pure water cleaning of the steel wire to obtain activated steel wire; sequentially preheating, hot-dip galvanizing, air knife thickness control, and cooling treatment of the activated steel wire to form a galvanized layer on the surface of the steel wire to obtain a crude galvanized steel wire; and then sequentially passivating and sealing with chromium-free passivation solution, surface conditioning solution treatment, hot pure water cleaning, and high-pressure hot air drying to obtain galvanized steel wire.

[0020] Furthermore, in step S5, the outer sheath material is polyvinyl chloride, and the extrusion thickness is 2.0-4.0 mm.

[0021] The present invention has the following beneficial effects: 1. In this invention, the carbazole group in the olefin-modified hybrid siloxane constructs a deep-level charge trap through conjugated heterocycles. The trifluoropropyl group and phenyl group co-condense to form a fluorosilicone-aromatic hybrid polysiloxane network. The two work together to suppress space charge accumulation and enhance chain segment rigidity. The methacryloyloxy group is in-situ grafted and crosslinked with polyethylene under the initiation of peroxide, constructing an organic-inorganic interpenetrating network in the matrix. The charge trap, rigid network and interpenetrating network are coupled, effectively dispersing electrical tree channels and inhibiting crack propagation under a strong electric field, which significantly improves the impact breakdown voltage and power frequency electrical strength per unit thickness of the insulation layer.

[0022] 2. In this invention, the methacryloyloxy group of the olefin-modified hybrid siloxane side chain is in-situ grafted and crosslinked with polyethylene under the initiation of peroxide, constructing an organic-inorganic interpenetrating network in the matrix. This allows the hybrid siloxane to be chemically anchored within the polyethylene phase, avoiding interface defects caused by physical blending. The interpenetrating network works synergistically with the rigid segments of the carbazole-based hybrid polysiloxane. Under mechanical load, through stress transfer and energy dissipation at the organic-inorganic phase interface, it effectively disperses electrical tree channels and inhibits crack propagation, thereby endowing the insulation layer with high impact resistance and crack resistance.

[0023] 3. In this invention, the fluorosilicone-aromatic hybrid polysiloxane network formed by the co-condensation of trifluoropropyl and phenyl imparts high rigidity to the chain segments, and the in-situ graft crosslinking of methacryloyloxy and polyethylene further constructs a three-dimensional network. The two work together to enhance low-temperature toughness and inhibit interfacial debonding. The coupling of this rigid hybrid chain segment with the chemical crosslinking network enables the insulation layer to maintain structural integrity under low-temperature winding conditions, thereby improving the toughness of the cable under low-temperature conditions. Detailed Implementation

[0024] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] The cross-linked polyethylene-based semiconductive shielding material used in this invention was purchased from Ningjin County Haoxin New Material Technology Co., Ltd., with model number ZJ-70℃, batch number hx147, and brand name Haoxin. The semiconducting resistive water tape used in this invention was purchased from Ningjin County Haoxin New Material Technology Co., Ltd., with a width of 80mm, grade HX-051, thickness of 0.3mm, and brand name Haoxin. The loosely woven copper mesh used in this invention was purchased from Anping County Dexiangrui Wire Mesh Co., Ltd., with an aperture of 0.37mm, a wire diameter of 0.13mm, and a model number of DXRt6. The low-density polyethylene used in the lining material of this invention was purchased from Dongguan Julong Plastic Raw Materials Co., Ltd., with the grade HP0722N, a melt flow rate of 0.75g / 10min, and the brand name SABIC. The low-density polyethylene used as insulation material in this invention was purchased from Shanghai Shabak International Trade Co., Ltd., with the grade DFDJ4960 and the brand name Euca Japan. The polyvinyl chloride used in the outer sheath material of this invention was purchased from Suzhou Zhihuiying New Material Technology Co., Ltd., with the grade PA5470 / 5 and the brand vinnolit from Germany. The chromium-free passivation solution used in this invention was purchased from Nanjing Xuanhao New Material Technology Co., Ltd., with brand name AW-615 and model name NH-1189.

[0026] Example 1 This embodiment provides a method for preparing olefin-modified hybrid siloxanes, including the following steps: Step I: Preparation of carbazole siloxane intermediate Weigh 85g of 3-amino-9-ethylcarbazole and 1500mL of toluene and place them in a reaction vessel under nitrogen atmosphere and stir. Add 230g of 3-[(2,3)-epoxypropoxy]propylmethyldimethoxysilane and 2g of salicylic acid. Heat the reaction vessel to 110℃ and keep it at that temperature for 16h. After the reaction is complete, wait for the reaction solution to cool to 50℃, filter to remove insoluble matter, and transfer the filtrate to a rotary evaporator at 60℃. Evaporate under reduced pressure until no liquid is collected to obtain carbazole siloxane intermediate.

[0027] Step II: Preparation of carbazole-based hybrid polysiloxane Weigh 200g of carbazole-based siloxane intermediate and 800mL of toluene and place them in a reaction vessel and stir. Add 20g of trifluoropropyltrimethoxysilane and 30g of methylphenyldimethoxysilane and stir at room temperature for 10min. Add 200mL of ethanol and 50mL of deionized water and stir at room temperature for 30min. Add 0.6g of dibutyltin dilaurate. Heat the reaction vessel to 50℃ and keep it at that temperature for 1h. Then heat the reaction vessel to 75℃ and keep it at that temperature for 3h. After the reaction is complete, let the reaction system cool to room temperature and transfer it to a rotary evaporator at 50℃. Remove the solvent by rotary evaporation under reduced pressure to obtain carbazole-based hybrid polysiloxane.

[0028] Step III: Preparation of olefin-modified hybrid siloxanes Weigh 240g of carbazole-modified polysiloxane and 1500mL of dichloromethane and place them in a nitrogen-protected reactor with stirring. Add 45g of triethylamine, 1.5g of 4-dimethylaminopyridine and 0.15g of hydroquinone monomethyl ether. Place the reactor in an ice bath at 0°C and add 40g of methacryloyl chloride. Allow the reactor to return to room temperature and react in the dark for 6 hours. After the reaction is complete, allow the reaction system to cool to 0°C and slowly add saturated sodium bicarbonate aqueous solution to neutralize it. Transfer the reaction solution to a separatory funnel. Wash the organic phase once with deionized water and once with saturated brine. Dry with anhydrous sodium sulfate and filter. Transfer the solution to a rotary evaporator at 35°C and evaporate under reduced pressure in the dark until no liquid is collected to obtain olefin-modified hybrid siloxane.

[0029] The amino group of 3-amino-9-ethylcarbazole undergoes ring-opening addition with the epoxy group of 3-[(2,3)-epoxypropoxy]propylmethyldimethoxysilane to generate a siloxane monomer containing carbazole and hydroxyl groups. This monomer, along with trifluoropropyltrimethoxysilane and methylphenyldimethoxysilane, undergoes hydrolytic condensation under the catalysis of dibutyltin dilaurate to form a hybrid polysiloxane containing carbazole, trifluoropropyl, and phenyl groups. The hydroxyl groups on the side chains of the polysiloxane undergo esterification with methacryloyl chloride to introduce olefin unsaturated double bonds, resulting in olefin-modified hybrid siloxanes.

[0030] The carbazole group endows the siloxane with a conjugated heterocyclic structure, constructing a deep-level charge trap to inhibit the accumulation of space charge in the polyethylene matrix. The trifluoropropyl group and phenyl group co-condense to form a fluorosilicone-aromatic hybrid polysiloxane network, which enhances the rigidity of the chain segments and the hydrophobic barrier, and reduces dielectric loss. The methacryloyloxy group provides olefin grafting sites, which are then in-situ grafted and crosslinked with polyethylene through oxide initiation to construct an organic-inorganic interpenetrating network, which disperses electrical tree channels and inhibits the propagation of impact cracks.

[0031] Example 2 This embodiment provides a method for preparing olefin-modified hybrid siloxanes, including the following steps: Step I: Preparation of carbazole siloxane intermediate Weigh 90g of 3-amino-9-ethylcarbazole and 1750mL of toluene and place them in a reaction vessel under nitrogen atmosphere and stir. Add 240g of 3-[(2,3)-epoxypropoxy]propylmethyldimethoxysilane and 3.5g of salicylic acid. Heat the reaction vessel to 115℃ and keep it at that temperature for 18h. After the reaction is complete, wait for the reaction solution to cool to 55℃, filter to remove insoluble matter, and transfer the filtrate to a rotary evaporator at 65℃. Evaporate under reduced pressure until no liquid is collected to obtain carbazole siloxane intermediate.

[0032] Step II: Preparation of carbazole-based hybrid polysiloxane Weigh 210 g of carbazole-based siloxane intermediate and 1000 mL of toluene and place them in a reaction vessel and stir. Add 35 g of trifluoropropyltrimethoxysilane and 50 g of methylphenyldimethoxysilane and stir at room temperature for 15 min. Add 250 mL of ethanol and 65 mL of deionized water and stir at room temperature for 45 min. Add 0.9 g of dibutyltin dilaurate. Heat the reaction vessel to 55 °C and keep it at that temperature for 1.5 h. Then heat the reaction vessel to 80 °C and keep it at that temperature for 4 h. After the reaction is complete, let the reaction system cool to room temperature and transfer it to a rotary evaporator at 55 °C. Remove the solvent by rotary evaporation under reduced pressure to obtain carbazole-based hybrid polysiloxane.

[0033] Step III: Preparation of olefin-modified hybrid siloxanes Weigh 250g of carbazole-modified polysiloxane and 2000mL of dichloromethane and place them in a nitrogen-protected reactor with stirring. Add 55g of triethylamine, 2g of 4-dimethylaminopyridine and 0.22g of hydroquinone monomethyl ether. Place the reactor in an ice bath at 3°C ​​and add 50g of methacryloyl chloride. Allow the reactor to return to room temperature and react in the dark for 9 hours. After the reaction is complete, allow the reaction system to cool to 5°C and slowly add saturated sodium bicarbonate aqueous solution to neutralize it. Transfer the reaction solution to a separatory funnel. Wash the organic phase twice with deionized water and saturated brine, dry it with anhydrous sodium sulfate, filter it, and transfer it to a rotary evaporator at 40°C. Evaporate under reduced pressure in the dark until no liquid is collected to obtain olefin-modified hybrid siloxane.

[0034] Example 3 This embodiment provides a method for preparing olefin-modified hybrid siloxanes, including the following steps: Step I: Preparation of carbazole siloxane intermediate Weigh 95g of 3-amino-9-ethylcarbazole and 2000mL of toluene and place them in a reaction vessel under nitrogen atmosphere and stir. Add 250g of 3-[(2,3)-epoxypropoxy]propylmethyldimethoxysilane and 5g of salicylic acid. Heat the reaction vessel to 120℃ and keep it at that temperature for 20h. After the reaction is complete, wait for the reaction solution to drop to 60℃, filter to remove insoluble matter, and transfer the filtrate to a rotary evaporator at 70℃. Evaporate under reduced pressure until no liquid is collected to obtain carbazole siloxane intermediate.

[0035] Step II: Preparation of carbazole-based hybrid polysiloxane Weigh 220 g of carbazole-based siloxane intermediate and 1200 mL of toluene and place them in a reaction vessel and stir. Add 50 g of trifluoropropyltrimethoxysilane and 70 g of methylphenyldimethoxysilane and stir at room temperature for 20 min. Add 300 mL of ethanol and 80 mL of deionized water and stir at room temperature for 60 min. Add 1.2 g of dibutyltin dilaurate. Heat the reaction vessel to 60 °C and keep it at that temperature for 2 h. Then heat the reaction vessel to 85 °C and keep it at that temperature for 5 h. After the reaction is complete, let the reaction system cool to room temperature and transfer it to a rotary evaporator at 60 °C. Remove the solvent by rotary evaporation under reduced pressure to obtain carbazole-based hybrid polysiloxane.

[0036] Step III: Preparation of olefin-modified hybrid siloxanes Weigh 260g of carbazole-modified polysiloxane and 2500mL of dichloromethane and place them in a nitrogen-protected reactor with stirring. Add 65g of triethylamine, 2.5g of 4-dimethylaminopyridine and 0.30g of hydroquinone monomethyl ether. Keep the reactor in an ice bath at 5°C. Add 60g of methacryloyl chloride and allow it to recover to room temperature and react in the dark for 12 hours. After the reaction is complete, let the reaction system cool to 10°C and slowly add saturated sodium bicarbonate aqueous solution to neutralize it. Transfer the reaction solution to a separatory funnel. Wash the organic phase three times with deionized water and saturated brine, dry it with anhydrous sodium sulfate, filter it, and transfer it to a rotary evaporator at 45°C. Evaporate under reduced pressure in the dark until no liquid is collected to obtain olefin-modified hybrid siloxane.

[0037] Example 4 This embodiment provides a method for preparing an insulating material, including the following steps: Step ①: Preparation of modified polyethylene particles Weigh out 800g of low-density polyethylene and 80g of olefin-modified hybrid siloxane, mix them evenly in a high-speed mixer, transfer them to a twin-screw extruder for melt blending, extrusion and granulation to obtain modified polyethylene granules.

[0038] Step 2: Preparation of insulating material Weigh 900g of modified polyethylene granules and 0.5g of dicumyl peroxide and place them in a reaction vessel. Mix them and heat the reaction vessel to 50℃. Mix and absorb for 2 hours. After the mixing and absorption are completed, the product is cooled, granulated, and vacuum dried at 40℃ for 4 hours. It is then sealed and stored to obtain the insulating material.

[0039] Low-density polyethylene and olefin-modified hybrid siloxanes are melt-blended to achieve uniform dispersion and in-situ grafting of the hybrid siloxanes in the polyethylene matrix, resulting in modified polyethylene particles. The modified polyethylene particles and dicumyl peroxide are then subjected to isothermal absorption, allowing the peroxide to penetrate and distribute uniformly within the particles, thus obtaining a crosslinkable insulating material.

[0040] Melt blending allows carbazole-based hybrid siloxanes to be uniformly dispersed in the polyethylene matrix and form in-situ grafts, constructing an organic-inorganic hybrid network, inhibiting space charge accumulation and dispersing electrical tree channels. The isothermal absorption of peroxides allows the crosslinking agent to penetrate uniformly into the particle interior, providing uniformly distributed initiation sites for subsequent crosslinking, forming a three-dimensional network to inhibit crack propagation.

[0041] Example 5 This embodiment provides a method for preparing an insulating material, including the following steps: Step ①: Preparation of modified polyethylene particles Weigh out 900g of low-density polyethylene and 110g of olefin-modified hybrid siloxane, mix them evenly in a high-speed mixer, transfer them to a twin-screw extruder for melt blending, extrusion and granulation to obtain modified polyethylene granules.

[0042] Step 2: Preparation of insulating material Weigh out 950g of modified polyethylene granules and 0.75g of dicumyl peroxide and place them in a reaction vessel. Mix them and heat the reaction vessel to 60℃. Mix and absorb for 4 hours. After the mixing and absorption are completed, the product is cooled, granulated, and vacuum dried at 45℃ for 6 hours. It is then sealed and stored to obtain the insulating material.

[0043] Example 6 This embodiment provides a method for preparing an insulating material, including the following steps: Step ①: Preparation of modified polyethylene particles Weigh out 1000g of low-density polyethylene and 150g of olefin-modified hybrid siloxane, mix them evenly in a high-speed mixer, transfer them to a twin-screw extruder for melt blending, extrusion and granulation to obtain modified polyethylene granules.

[0044] Step 2: Preparation of insulating material Weigh 1000g of modified polyethylene granules and 1g of dicumyl peroxide and place them in a reaction vessel. Mix them and heat the reaction vessel to 70℃. Mix and absorb for 6 hours. After the mixing and absorption are completed, the product is cooled, granulated, and vacuum dried at 50℃ for 8 hours. It is then sealed and stored to obtain the insulating material.

[0045] Example 7 This embodiment provides a method for preparing an insulated, impact-resistant medium-voltage power cable, including the following steps: Step 1: Preparation of cable core conductor Multiple strands of annealed copper wire are tightly twisted into a circular shape to obtain the cable core conductor.

[0046] Step 2: Preparing the Insulated Wire Core The semiconductive shielding material, the insulating material prepared in Example 4, and the outer semiconductive shielding material were simultaneously extruded onto the outside of the cable core conductor using a three-layer co-extrusion equipment. The extrusion thickness of the semiconductive shielding material was controlled to be 0.5 mm, the extrusion thickness of the insulating material was 2.5 mm, and the extrusion thickness of the outer semiconductive shielding material was 0.5 mm. The extrusion temperature of the three-layer co-extrusion was 180°C. The material was then transferred to a cross-linking tube for steam cross-linking at a temperature of 300°C. After cooling and shaping, the insulated wire core was obtained.

[0047] Step 3: Prepare the metal shielding layer The semiconducting resistive water tape is wrapped around the outside of the insulated wire core, one layer is wrapped, and then a loosely woven copper mesh is wrapped around it to obtain a metal shielding layer.

[0048] Step 4: Prepare the galvanized steel wire armor layer The steel wire was immersed in a 10% hydrochloric acid aqueous solution and pickled at 20°C for 2 minutes. After pickling, it was rinsed with room temperature tap water for 1 minute until there was no obvious residual acid on the surface of the steel wire. Then the steel wire was transferred to an electrolytic activation tank, with the steel wire as the anode and a 5% sulfuric acid aqueous solution as the electrolyte. The anode micro-electrolytic activation treatment was carried out for 10 seconds under the conditions of a current density of 2A / dm2 and an electrolyte temperature of 20°C. Then it was rinsed with pure water with a conductivity of no more than 20μS / cm for 30 seconds to obtain the activated steel wire. The activated steel wire is preheated at 100℃ for 1 minute, and then immersed in zinc bath at 450℃ for hot-dip galvanizing treatment for 5 seconds. The zinc mass fraction in the zinc bath is not less than 99.5%. After the steel wire leaves the zinc bath, the excess zinc bath on the surface is scraped off by an air knife to form a galvanized layer with a thickness of 20μm on the surface of the steel wire. Then it is cooled to below 80℃ to obtain the coarse galvanized steel wire. Weigh out 0.8 parts sodium carbonate, 2.0 parts sodium bicarbonate and 97.2 parts deionized water by weight and place them in a mixing tank. Stir at 200 r / min for 15 min at room temperature. After the solids are completely dissolved, measure and fine-tune the pH to 7.5 using a precision pH meter to obtain the surface conditioning solution for later use. The coarse galvanized steel wire is immersed in a chromium-free passivation solution and passivated for 20 seconds at 20°C. After passivation, the wire is transported to a surface conditioning tank and treated with a surface conditioning solution with a pH of 7.5 for 20 seconds to make the residual treatment solution on the surface of the wire nearly neutral. Then, it is rinsed with hot pure water at 60°C with a conductivity of no more than 20 μS / cm for 30 seconds, and then dried with high-pressure hot air at 80°C and an outlet air velocity of 15 m / s for 1 minute to obtain galvanized steel wire for later use. Low-density polyethylene is extruded onto the outside of the metal shielding layer to form an inner lining layer; then, galvanized steel wire with a diameter of 1.0 mm is tightly wrapped around the outside of the inner lining layer with a wrapping pitch of 10 mm to obtain a galvanized steel wire armor layer.

[0049] Step 5: Prepare medium-voltage power cables with insulation and impact resistance. Polyvinyl chloride is extruded onto the outside of a galvanized steel wire armor layer, with the extrusion thickness controlled at 2.0 mm. After cooling and shaping in a water tank, an insulated and impact-resistant medium-voltage power cable is obtained.

[0050] Example 8 This embodiment provides a method for preparing an insulated, impact-resistant medium-voltage power cable, including the following steps: Step 1: Preparation of cable core conductor Multiple strands of annealed copper wire are tightly twisted into a circular shape to obtain the cable core conductor.

[0051] Step 2: Preparing the Insulated Wire Core The semiconductive shielding material, the insulating material prepared in Example 5, and the outer semiconductive shielding material were simultaneously extruded onto the outside of the cable core conductor using a three-layer co-extrusion equipment. The extrusion thickness of the semiconductive shielding material was controlled to be 0.75 mm, the extrusion thickness of the insulating material was 3.5 mm, and the extrusion thickness of the outer semiconductive shielding material was 0.75 mm. The extrusion temperature of the three-layer co-extrusion was 200°C. The material was then transferred to a cross-linking tube for steam cross-linking at a temperature of 350°C. After cooling and shaping, the insulated wire core was obtained.

[0052] Step 3: Prepare the metal shielding layer The semiconducting resistive water tape is wrapped around the outside of the insulated wire core, wrapped in two layers, and then covered with a loosely woven copper mesh to obtain a metal shielding layer.

[0053] Step 4: Prepare the galvanized steel wire armor layer The steel wire was immersed in a 12.5% ​​hydrochloric acid aqueous solution and pickled at 30°C for 3 minutes. After pickling, it was rinsed with room temperature tap water for 2 minutes until there was no obvious residual acid on the surface of the steel wire. Then the steel wire was transferred to an electrolytic activation tank, with the steel wire as the anode and a 7.5% sulfuric acid aqueous solution as the electrolyte. The anode micro-electrolytic activation treatment was carried out for 20 seconds under the conditions of a current density of 3.5A / dm2 and an electrolyte temperature of 28°C. After that, it was rinsed with pure water with a conductivity of no more than 20μS / cm for 45 seconds to obtain the activated steel wire. The activated steel wire is preheated at 125℃ for 2 minutes, and then immersed in zinc bath at 460℃ for hot-dip galvanizing treatment for 10 seconds. The zinc mass fraction in the zinc bath is not less than 99.5%. After the steel wire leaves the zinc bath, the excess zinc bath on the surface is scraped off by an air knife to form a zinc coating layer with a thickness of 35μm on the surface of the steel wire. Then it is cooled to below 80℃ to obtain the coarse galvanized steel wire. Weigh out 0.8 parts sodium carbonate, 2.0 parts sodium bicarbonate and 97.2 parts deionized water by weight and place them in a mixing tank. Stir at 200 r / min for 15 min at room temperature. After the solids are completely dissolved, measure and fine-tune the pH to 8.0 using a precision pH meter to obtain the surface conditioning solution for later use. The coarse galvanized steel wire is immersed in a chromium-free passivation solution and passivated at 30°C for 40 seconds. After passivation, the wire is transferred to a surface conditioning tank and treated with a surface conditioning solution with a pH of 8.0 for 30 seconds to make the residual treatment solution on the surface of the wire nearly neutral. Then, it is rinsed with hot pure water at 70°C with a conductivity of no more than 20 μS / cm for 45 seconds, and then dried with high-pressure hot air at 90°C and an outlet air velocity of 20 m / s for 2 minutes to obtain galvanized steel wire for later use. Low-density polyethylene is extruded onto the outside of the metal shielding layer to form an inner lining layer; then galvanized steel wire with a diameter of 2.0 mm is tightly wrapped around the outside of the inner lining layer with a wrapping pitch of 15 mm to obtain a galvanized steel wire armor layer.

[0054] Step 5: Prepare medium-voltage power cables with insulation and impact resistance. Polyvinyl chloride is extruded onto the outside of a galvanized steel wire armor layer, with the extrusion thickness controlled at 3.0 mm. After cooling and shaping in a water bath, an insulated and impact-resistant medium-voltage power cable is obtained.

[0055] Example 9 This embodiment provides a method for preparing an insulated, impact-resistant medium-voltage power cable, including the following steps: Step 1: Preparation of cable core conductor Multiple strands of annealed copper wire are tightly twisted into a circular shape to obtain the cable core conductor.

[0056] Step 2: Preparing the Insulated Wire Core The semiconductive shielding material, the insulating material prepared in Example 6, and the outer semiconductive shielding material were simultaneously extruded onto the outside of the cable core conductor using a three-layer co-extrusion equipment. The extrusion thickness of the semiconductive shielding material was controlled to be 1.0 mm, the extrusion thickness of the insulating material was 5.0 mm, and the extrusion thickness of the outer semiconductive shielding material was 1.0 mm. The extrusion temperature of the three-layer co-extrusion was 220°C. The material was then transferred to a cross-linking tube for steam cross-linking at a temperature of 400°C. After cooling and shaping, the insulated wire core was obtained.

[0057] Step 3: Prepare the metal shielding layer The semiconducting resistive water tape is wrapped around the outside of the insulated wire core, wrapped in two layers, and then covered with a loosely woven copper mesh to obtain a metal shielding layer.

[0058] Step 4: Prepare the galvanized steel wire armor layer The steel wire was immersed in a 15% hydrochloric acid aqueous solution and pickled at 35°C for 5 minutes. After pickling, it was rinsed with room temperature tap water for 3 minutes until there was no obvious residual acid on the surface of the steel wire. Then the steel wire was transferred to an electrolytic activation tank, with the steel wire as the anode and a 10% sulfuric acid aqueous solution as the electrolyte. The anode micro-electrolytic activation treatment was carried out for 30 seconds under the conditions of a current density of 5A / dm2 and an electrolyte temperature of 35°C. After that, it was rinsed with pure water with a conductivity of no more than 20μS / cm for 60 seconds to obtain the activated steel wire. Weigh out 0.8 parts sodium carbonate, 2.0 parts sodium bicarbonate and 97.2 parts deionized water by weight and place them in a mixing tank. Stir at 200 r / min for 15 min at room temperature. After the solids are completely dissolved, measure and fine-tune the pH to 8.5 using a precision pH meter to obtain the surface conditioning solution for later use. The activated steel wire is preheated at 150°C for 3 minutes, and then immersed in a zinc bath at 470°C for hot-dip galvanizing for 15 seconds. The zinc mass fraction in the zinc bath is not less than 99.5%. After the steel wire leaves the zinc bath, the excess zinc bath on the surface is scraped off by an air knife to form a galvanized layer with a thickness of 50 μm on the surface of the steel wire. Then it is cooled to below 80°C to obtain a coarse galvanized steel wire. The coarse galvanized steel wire is immersed in a chromium-free passivation solution and passivated at 40°C for 60 seconds. After passivation, the wire is transported to a surface conditioning tank and treated with a surface conditioning solution with a pH of 8.5 for 40 seconds to make the residual treatment solution on the surface of the wire nearly neutral. Then, it is rinsed with hot pure water at 80°C with a conductivity of no more than 20 μS / cm for 60 seconds, and then dried with high-pressure hot air at 100°C and an outlet air velocity of 25 m / s for 3 minutes to obtain galvanized steel wire for later use. Low-density polyethylene is extruded onto the outside of the metal shielding layer to form an inner lining layer; then galvanized steel wire with a diameter of 2.5 mm is tightly wrapped around the outside of the inner lining layer with a wrapping pitch of 20 mm to obtain a galvanized steel wire armor layer.

[0059] Step 5: Prepare medium-voltage power cables with insulation and impact resistance. Polyvinyl chloride is extruded onto the outside of a galvanized steel wire armor layer, with the extrusion thickness controlled at 4.0 mm. After cooling and shaping in a water tank, an insulated and impact-resistant medium-voltage power cable is obtained.

[0060] Comparative Example 1 The difference between this comparative example and Example 9 is that, in step ① when preparing modified polyethylene particles, an equal amount of carbazole siloxane intermediate is used to replace the olefin-modified hybrid siloxane.

[0061] Comparative Example 2 The difference between this comparative example and Example 9 is that, in step ① when preparing modified polyethylene particles, carbazole-based hybrid polysiloxane is used in an equal amount to replace olefin-modified hybrid siloxane.

[0062] Performance testing: Impulse voltage test: The insulated cores prepared in Examples 7-9 and Comparative Examples 1-2 were subjected to impulse voltage test according to standard GB / T 3048.13 "Electrical performance test methods for wires and cables - Part 13: Impulse voltage test". A section of the outer semiconductive shielding layer at both ends of the insulated core sample was removed to prevent surface flashover. The outer semiconductive shielding layer was grounded. A standard lightning impulse wave was applied between the core conductor and the outer semiconductive shielding layer. The wavefront time was 1.2 μs and the half-wave time was 50 μs. The voltage was gradually increased until the sample broke down. The impulse breakdown voltage was recorded and converted into the impulse breakdown strength per unit thickness according to the actual thickness of the insulation layer. The unit is kV / mm. Power frequency breakdown strength: In accordance with standard GB / T 1408.1-2016 "Electrical strength test method for insulating materials - Part 1: Test under power frequency", the insulation layer was stripped from the insulated wire cores prepared in Examples 7-9 and Comparative Examples 1-2 and standard samples were made. Power frequency voltage was applied in transformer oil medium by continuous uniform voltage increase method. The test environment was (23±2)℃. The power frequency electrical strength was characterized, and the unit was kV / mm. Low-temperature winding test: The insulated wire cores prepared in Examples 7-9 and Comparative Examples 1-2 were subjected to a low-temperature winding test in accordance with the standard GB / T 2951.14-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers - Part 14: General Test Methods - Low Temperature Test". The insulated wire core sample and a test rod with a diameter of 4-5 times the outer diameter of the sample were placed in a low-temperature chamber and cooled at (-15±2)℃ for a specified time. After cooling, the wire core was wound into a tight spiral on the test rod at a rate of about 5s / turn. After returning to room temperature, the wire core was inspected with normal vision and characterized by the absence of cracks on the surface of the insulated wire core. Partial discharge test: Partial discharge tests were conducted on the insulated cores prepared in Examples 7-9 and Comparative Examples 1-2 in accordance with standard GB / T 3048.12-2025 "Test Methods for Electrical Properties of Wires and Cables - Part 12: Partial Discharge Test". The test voltage was applied between the core conductor and the outer semiconductive shielding layer, which was grounded. The voltage was first increased to 2U0 and held for 10s, and then slowly reduced to 1.73U0. The partial discharge quantity was measured at this voltage and characterized by the partial discharge quantity in pC. The specific data are shown in Table 1.

[0063] Table 1 - Performance Test Data for Each Sample Data Analysis: A comparative analysis of the above table shows that the insulated wire core prepared by this invention has a unit thickness impact breakdown voltage of 75.8kV / mm, a power frequency electrical strength of 41.4kV / mm, and a partial discharge of 1.7pC. At the same time, it does not crack after being wound 3 turns. All data are better than the comparative example. Compared with Example 9, the unit thickness impact breakdown strength and power frequency electrical strength of Comparative Example 1 were significantly reduced, the partial discharge was significantly increased and exceeded the conventional judgment limit, and cracks appeared after low temperature winding. The reason is that the carbazole-based siloxane intermediate is a small molecule monomer without a hybrid polysiloxane network and olefin grafting sites, and cannot be anchored to the polyethylene matrix. The residual methoxy condensation volatilization forms micropores, which become both a source of partial discharge and a weak point for electron avalanche under electric field. The carbazole charge trap is also weakened because it cannot be uniformly fixed. The micropores cause stress concentration under low temperature bending, resulting in surface cracking.

[0064] Compared with Example 9, Comparative Example 2 showed a decrease in unit thickness impact breakdown strength and power frequency electrical strength, and an increase in partial discharge, but no cracks after low-temperature winding, making it superior to Comparative Example 1 overall. The reason is that the carbazole-based hybrid polysiloxane retains the fluorosilicone aromatic hybrid network and carbazole charge trap, and its low-temperature flexibility and space charge suppression effect are still present; however, it lacks methacryloyloxy grafting sites and cannot be grafted in situ with polyethylene, relying only on physical blending. The interface defects weaken the dispersion of electrical trees and crack blocking effect of the interpenetrating network.

[0065] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. An insulated, impact-resistant medium-voltage power cable, comprising several sets of insulated conductors, characterized in that, The insulated core is obtained by co-extruding three layers of semi-conductive shielding material, insulating material and outer semi-conductive shielding material onto the outside of the cable core conductor. The insulating material is prepared by the following steps: A1. Low-density polyethylene and olefin-modified hybrid siloxane are mixed evenly in a high-speed mixer, then transferred to a twin-screw extruder for melt blending, extrusion and granulation to obtain modified polyethylene granules. A2. The modified polyethylene particles and the initiator are placed in a reaction vessel and mixed. The reaction vessel is heated to 50-70℃ and the mixture is absorbed for 2-6 hours. The insulation material is then obtained through post-treatment.

2. The medium-voltage power cable with insulation and impact resistance according to claim 1, characterized in that, The medium-voltage power cable also includes a metal shielding layer, an inner lining layer, a galvanized steel wire armor layer, and an outer sheath layer.

3. The medium-voltage power cable with insulation and impact resistance according to claim 1, characterized in that, In step A1, the weight ratio of the low-density polyethylene to the olefin-modified hybrid siloxane is (80-100):(8-15); in step A2, the weight ratio of the modified polyethylene particles to the initiator is (90-100):(0.05-0.1), and the initiator is one or both of dicumyl peroxide and 2,5-dimethyl-2,5-di-tert-butylperoxide.

4. The medium-voltage power cable with insulation and impact resistance according to claim 1, characterized in that, The olefin-modified hybrid siloxane was prepared by the following steps: B1. Place 3-amino-9-ethylcarbazole and toluene in a reaction vessel under nitrogen atmosphere and stir. Add 3-[(2,3)-epoxypropoxy]propylmethyldimethoxysilane and salicylic acid. Heat the reaction vessel to 110-120℃ and keep it at the temperature for 16-20h. After post-treatment, carbazole siloxane intermediate is obtained. B2. Place the carbazole-based siloxane intermediate and toluene in a reaction vessel and stir. Add trifluoropropyltrimethoxysilane and methylphenyldimethoxysilane, stir at room temperature for 10-20 min, add ethanol and deionized water, stir at room temperature for 30-60 min, add dibutyltin dilaurate, heat the reaction vessel to 50-60℃, keep the reaction at this temperature for 1-2 h, then heat the reaction vessel to 75-85℃, keep the reaction at this temperature for 3-5 h, and then perform post-treatment to obtain carbazole-based hybrid polysiloxane. B3. Carbazole-modified polysiloxane and dichloromethane were placed in a nitrogen-protected reactor and stirred. Triethylamine, 4-dimethylaminopyridine and hydroquinone monomethyl ether were added. The reactor was kept in an ice bath at 0-5°C. Methacrylamide chloride was added. The reactor was allowed to return to room temperature and reacted in the dark for 6-12 hours. The olefin-modified hybrid siloxane was then obtained after post-treatment.

5. The medium-voltage power cable with insulation and impact resistance according to claim 4, characterized in that, In step B1, the ratio of the amounts of 3-amino-9-ethylcarbazole, toluene, 3-[(2,3)-epoxypropoxy]propylmethyldimethoxysilane and salicylic acid is (8.5-9.5)g:(150-200)mL:(23-25)g:(0.2-0.5)g.

6. The medium-voltage power cable with insulation and impact resistance according to claim 4, characterized in that, In step B2, the ratio of the carbazolylsiloxane intermediate, toluene, trifluoropropyltrimethoxysilane, methylphenyldimethoxysilane, ethanol, deionized water and dibutyltin dilaurate is (20-22)g:(80-120)mL:(2-5)g:(3-7)g:(20-30)mL:(5-8)mL:(0.06-0.12)g.

7. The medium-voltage power cable with insulation and impact resistance according to claim 4, characterized in that, In step B3, the ratio of the carbazole-based hybrid polysiloxane, dichloromethane, triethylamine, 4-dimethylaminopyridine, hydroquinone monomethyl ether, and methacryloyl chloride is (24-26) g:(150-250) mL:(4.5-6.5) g:(0.15-0.25) g:(0.015-0.030) g:(4-6) g.

8. A method for preparing an insulated, impact-resistant medium-voltage power cable as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Multiple strands of annealed copper wire are tightly twisted into a circular shape to obtain the cable core conductor; S2. Semiconductor shielding material, insulating material and outer semiconductor shielding material are simultaneously extruded onto the outside of the cable core conductor using a three-layer co-extrusion device, and then transferred to a cross-linking tube for heating cross-linking and cooling shaping to obtain an insulated wire core; the insulating material includes low-density polyethylene, olefin-modified hybrid siloxane and initiator. S3. Wrap the semiconducting resistive water tape around the outside of several sets of insulated wire cores, and then cover it with a loosely woven copper mesh to obtain a metal shielding layer. S4. Extrude the inner lining material onto the outside of the metal shielding layer to form the inner lining layer, and then tightly wrap the galvanized steel wire around the outside of the inner lining layer to obtain the galvanized steel wire armor layer. S5. The outer sheath material is extruded onto the outside of the galvanized steel wire armor layer, and after being cooled and shaped in a water tank, an insulated and impact-resistant medium-voltage power cable is obtained.

9. A method for preparing an insulated, impact-resistant medium-voltage power cable according to claim 8, characterized in that, In step S2, the extrusion thickness of the insulating material is 2.5-5.0 mm, the extrusion temperature of the three-layer co-extrusion is 180-220℃, and the heating crosslinking is steam crosslinking at a temperature of 300-400℃; in step S3, the semiconducting resistance water tape is wrapped in 1-2 layers; in step S4, the inner lining material is low-density polyethylene, the diameter of the galvanized steel wire is 1.0-2.5 mm, and the wrapping pitch is 10-20 mm; in step S5, the outer sheath material is polyvinyl chloride, and the extrusion thickness is 2.0-4.0 mm.